Transcriptome profiling reveals functional variation in Plasmodium falciparum parasites from controlled human malaria infection studies - Hoo, Regina (2020)
Background: The transcriptome of Plasmodium falciparum clinical isolates varies according to strain, mosquito bites, disease severity and clinical history. Therefore, it remains a challenge to directly interpret the parasite's transcriptomic information into a more general biological signature in a natural human malaria infection. These confounding variations can be potentially overcome with parasites derived from controlled-human malaria infection (CHMI) studies. Methods: We performed CHMI studies in healthy and immunologically naïve volunteers receiving the same P. falciparum strain ((Sanaria® PfSPZ Challenge (NF54)), but with different sporozoite dosage and route of infection. Parasites isolated from these volunteers at the day of patency were subjected to in vitro culture for several generations and synchronized ring-stage parasites were subjected to transcriptome profiling. Findings: We observed clear deviations between CHMI-derived parasites from volunteer groups receiving different PfSPZ dose and route. CHMI-derived parasites and the pre-mosquito strain used for PfSPZ generation showed significant transcriptional variability for gene clusters associated with malaria pathogenesis, immune evasion and transmission. These transcriptional variation signature clusters were also observed in the transcriptome of P. falciparum isolates from acute clinical infections. Interpretation: Our work identifies a previously unrecognized transcriptional pattern in malaria infections in a non-immune background. Significant transcriptome heterogeneity exits between parasites derived from human infections and the pre-mosquito strain, implying that the malaria parasites undergo a change in functional state to adapt to its host environment. Our work also highlights the potential use of transcriptomics data from CHMI study advance our understanding of malaria parasite adaptation and transmission in humans.